Bismuth Vanadium Oxide Can Promote Growth and Activity in Arabidopsis thaliana - Gao, Cong; Lu, Shuai; Wang, Yongzhou; Xu, Hao; Gao, Xiaoxiao; Gu, Yiwen; Xuan, Hongyun; Wang, Baohua; Yuan, Huihua; Cao, Yunying (Frontiers in Chemistry, 2021)
The excellent properties of nanomaterials have been confirmed in many fields, but the effects on plants are still unclear. In this study, different concentrations of bismuth vanadate (BV) were added to growth medium to analyse the growth of seedlings, including taproots, lateral roots, leaf stomata, root activity and superoxide anion O2.− generation. Gene expression levels related to root growth were determined by quantitative PCR in Arabidopsis thaliana. The results showed that BV promoted the growth of taproots, and the development of lateral roots, enhanced the length of the extension zone in roots, increased the number and size of leaf stomata and root activity, reduced the accumulation of reactive oxygen species in seedlings, and changed the expression levels related to polyamines or hormones. At the same time, we investigated the antibacterial activity of BV against a variety of common pathogens causing crop diseases. The results showed that BV could effectively inhibit the growth of cotton Fusarium wilt and rice sheath blight. These results provide a new prospect for the development of nanomaterial-assisted plants, which is expected to become one of the ways to solve the problem of controlling and promoting the development of plants. At the same time, it also provides a reference for the study of the effect of BV on plants.